Managing affect in interpreter-mediated institutional talk: examples from the medical setting - Letizia Cirillo (JoSTrans: The Journal of Specialised Translation)
The present paper sets out to explore ways in which affectivity surfaces and is dealt with in interpreter-mediated doctor-patient talk. Section 1 briefly discusses previous work on doctor-patient talk with and without the mediation of an interpreter. Section 2 sheds some light on the concept of affect. Section 3 includes a description of the data analysed and the methodological approach adopted. Section 4 offers a close investigation of five interactional sequences containing affective cues. Finally, Section 5 draws some conclusions regarding the role of interpreters in managing affective displays within conventionalised forms of interaction.1